Analisis Digital Literacy dan Compatibility terhadap Efektivitas Penggunaan Akuntansi Digital pada UMKM - Nastiti Rizky Shiyammurti; Irfan Sophan Himawan; Jejen Jaenudin; Diana Widhi Rachmawati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study examines digital literacy and compatibility and their influence on the effectiveness of digital accounting use in MSMEs. Data collection was carried out by distributing questionnaires to MSMEs in Cimahi City, totaling 97 MSMEs. Data processing used multiple regression analysis by first ensuring that the data was normally distributed. The results of the Kolmogorov test stated that the data collected in the study were normally distributed. The results of the partial analysis revealed that digital literacy had a positive and significant impact on the effectiveness of digital accounting use. Likewise, the results of the compatibility test gave a positive and significant influence on the use of digital accounting in MSMEs. Partially, the results of the study revealed that digital literacy and compatibility had a positive and significant effect on the effectiveness of digital accounting use. Thus, the importance of digital literacy for business actors and compatibility between the technology used and the business processes carried out.